Optimization of Lycopene Extraction from Tomato Pomace and Effect of Extract on Oxidative Stability of Peanut Oil - Dinh Thi Tran; Lan Thi Hoang Nguyen; Cuong Ngoc Nguyen; Maarten L. A. T. M. Hertog; Bart Nicolaï; David Picha (Polish Journal of Food and Nutrition Sciences)
Lycopene, the pigment principally responsible for the red color of tomatoes, is well-known for its strong antioxidant property and substantial health benefits. In this study, the optimal combination of factors for lycopene extraction from tomato pomace was identified using response surface methodology. The best practically feasible results maximizing both lycopene yield and antioxidant activity of the extract were obtained by applying a ratio of ethyl acetate to tomato waste of 35:1 (v/w), at a temperature of 55ºC for 100 min of extraction. The extract was then added to the peanut oil to evaluate its oxidative stability during 60 days of storage at 40ºC. It was shown that the addition of 2 g extract/kg oil offered the lowest level of peroxide value, p-anisidine value, and total oxidation value, followed by the oils with 50 mg butylated hydroxytoulene/kg oil and 1 g extract/kg oil, indicating the effect of lycopene-rich extract on enhancing the oxidative stability of peanut oil. The results in this study suggest that incorporation of extract rich in lycopene from tomato waste products may be an effective method to reduce oxidation and extend the shelf-life of peanut and other vegetable oils.